Analysis of Maternal Knowledge and Complementary Feeding Patterns as Risk Factors for Stunting in Children Aged 6-24 Months - Syahputra Yamin, Imam; Tania Fidzikri, Nanda Berliana; Effendi, Julham; Tamara, Metha Dwi; Rahmawati, Santi Deliani (Rifa'Institute, 2026)
Introduction: Nutritional status during the critical period of 6–24 months relies heavily on appropriate Complementary Feeding (MP-ASI), a practice directly modulated by maternal health literacy. Objective: This study analyzed the correlation between maternal knowledge levels and complementary feeding patterns with the nutritional status of children aged 6–24 months in Central Lombok Regency. Method: This cross-sectional study involved 73 mothers selected via consecutive sampling in the Penujak Public Health Center area. Maternal knowledge and feeding patterns were assessed using validated questionnaires, while nutritional status (Length-for-Age) was derived from secondary data. Data were analyzed using the Spearman’s rho test. Result and Discussion: Stunting prevalence was critically high at 57.5%. Most mothers (50.7%) had 'moderate' knowledge. Bivariate analysis revealed a significant positive correlation between maternal knowledge and nutritional status (r=0.297; p=0.011). Furthermore, a moderately strong correlation was found between complementary feeding patterns and nutritional status (r=0.531; p<0.001). Conclusion: Complementary feeding practices serve as a stronger determinant of nutritional status than knowledge alone. Interventions must shift from passive education to operational strategies, such as cooking demonstrations of local menus and the reactivation of Toddler Mothers’ Classes (Kelas Ibu Balita) to improve practical feeding skills.